Methylglyoxal, a reactive glucose metabolite, enhances autophagy flux and suppresses proliferation of human retinal pigment epithelial ARPE-19 cells. Issue 7 (October 2015) - Chang, Yo-Chen; Hsieh, Ming-Chu; Wu, Horng-Jiun; Wu, Wen-Chuan; Kao, Ying-Hsien
Highlights MGO suppresses ARPE-19 cell growth and potentiates H2O2-induced cytotoxicity. MGO enhances autophagy flux and autophagosome accumulation in ARPE-19 cells. Akt and MAPK signaling pathways are involved in MGO-elicited effect. Autophagy and kinase inhibitors ameliorate MGO-suppressed RPE cell growth. Autophagy and kinase inhibitors might be a therapeutic modality for AMD.